Kevaliditasan Instrumen Evaluasi dalam BSE Buku Teks Bahasa Indonesia Tahun Pelajaran 2019/2020 - Imam Safi'i; Fernanda Y. Listeini; Wini Tarmini (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2020)
This study aims to describe the level of validity of the evaluation instruments contained in the electronic school textbook (BSE) of Indonesian language textbooks for class IX in the 2019/2020 academic year. This research uses a qualitative approach. Determination of the sample in this study was conducted purposively, namely sampling by determining specific characteristics that are in accordance with the objectives of the study so that it is expected to answer the research problem. The sample in this study is in the form of an experimental report evaluation instrument. The validity data of the evaluation instruments collected included the material, construction, and language domains. The percentage of validity level is done by dividing the number of valid or invalid instruments by the number of validity criteria then multiplied by one hundred. Based on the research that has been done it can be known, that the evaluation instrument about writing a trial report has not fully fulfilled the validity element. The validity level of the evaluation instrument from the material domain is 25%, the construction realm is 68%, and the validity from the realm of language is 92%. The results of this study can be used as one of the foundations for evaluating and improving the quality of BSE Indonesian textbooks.